No fly zones and international security politics and strategy - Wrage, Stephen D.; Cooper, Scott A. (Military strategy and operational art, 2019)
This book discusses the practice of no-fly zones in international affairs. The first no-fly zone was imposed over northern Iraq immediately after the first Gulf War, and since then they have become a regular recourse for policymakers confronted with humanitarian crises. They have come to be viewed as a feasible, essentially non-violent form of intervention that can be performed entirely from the air in a situation where some form of action is widely thought to be necessary but the political will for a ground operation is insufficient. Nonetheless, even among policy makers there is limited understanding of the requirements, the shortcomings and the potentialities of no-fly zones. This is the first comprehensive work on this topic, and examines the assumptions surrounding no-fly zones by focusing on issues such as authority, cost, possibility of escalation and effectiveness. Looking back at 25 years of experience with no-fly zones, the book's goal is to look at what historical lessons may be drawn and to make some predictions with regard to the politics and strategy of no-fly zones in the future. This book will be of much interest to students of air power, security studies, Middle Eastern Studies and IR in general